Probiotic Properties of Exopolysaccharide-Producing Bacteria from Natto - Vongsathorn Ngampuak; Acharawan Thongmee; Napapan Pongpoungphet; Kanda Wongwailikhit; Panan Kanchanaphum (International Journal of Food Science)
Natto is a traditional Japanese food made from soybeans fermented with Bacillus subtilis var. natto. It is also a famous food in Thailand. Potential probiotics were screened from natto. Bacillus subtilis strain VN5 produced the most quantity of exopolysaccharide (EPS), so it was selected to study the properties of microbial EPS and probiotics. The Fourier transform infrared spectrometer or FT-IR spectroscopy confirmed the presence of carboxyl and hydroxyl groups. The patterns of FT-IR and levans are similar. The basic properties of probiotics were revealed. The 90% of VN5 strain resisted lysozyme within 30 min. VN5 survived under acidic conditions (pH 1-6), and the survival rate in 0.3%, 0.5%, and 1% bile solutions for 24 h was 100%. Unfortunately, VN5 did not inhibit the growth of Escherichia coli, Staphylococcus aureus, and Salmonella typhi. Gamma hemolysis was determined in VN5 strain. The finding on Bacillus subtilis strain (VN5) from natto paves the way to a high potential, useful new strain of probiotics.